Is Ejaculation Frequency in Men Related to General and Mental Health? Looking Back and Looking Forward - Mascherek, Anna; Reidick, Mirjam Christina; Gallinat, Jürgen; Kühn, Simone (Frontiers in Psychology, 2021)
Despite its relevance for human sexuality, literature on potential effects of ejaculation frequency and masturbation on general and mental health outcomes is sparse. Reasons for this knowledge gap include a general lack of interest, but also methodological challenges and still existing superstition. This paper reconciles literature from various fields to extract relevant information on how ejaculation frequency effects general and mental health outcomes. Culture-bound syndromes have been reported in countries still strictly tabooing or condemning masturbation. Masturbatory guilt describes a phenomenon in individuals experiencing a discrepancy between moral standards and own behavior with respect to masturbation. Abstinence is one aspect under study in the area of fertility treatment. Specific time frames and their respective implications on quality of sperm remain inconclusive. Limited temporal resolution capacities hamper the precise study of brain structures directly activated during ejaculation. The relation between ejaculation frequency and hormonal influences remains poorly understood. Future research that specifically addresses ejaculation frequency and potential mental and general health outcomes is needed. In contrast to extracting knowledge as a byproduct from other studies with a different focus, this enables sound study designs and could provide evidence-based results which could then be further discussed and interpreted.